Regulatory Effects of Chromium Picolinate and Phytochemicals on Blood Glucose via AMPK Pathway Activation - Joshi, Gaurav; Goutam, NIshant; Vashisht, Kanika; , Shivani; Kaur, Harmanbir; Kaur, Tejinder; Joshi, Neeraj (Scripta Medica, 2026)
The study examines the scientific work and clinical reports to emphasise the roles of Brassica juncea in glucose metabolism and glycogen synthesis, Gymnema sylvestre in insulin secretion and beta-cell regeneration and chromium picolinate in chromodulin synthesis and insulin receptor activation. Additionally, focus was placed on their combined ability to aggregate AMP-activated protein kinase (AMPK) signalling pathway, which play major role in insulin sensitivity and cellular energy homeostasis. By promoting glucose metabolism, chromium picolinate improves insulin sensitivity. By boosting insulin release and decreasing glucose absorption, Gymnema sylvestre helps manage diabetes. Glycogen production and enzyme activation are two ways that Brassica juncea aids in blood sugar management. When combined, these compounds enhance glucose absorption and decrease gluconeogenesis by activating the AMPK pathway. These synthetic and natural substances present encouraging diabetic treatment approaches. When combined with dietary changes, they can improve the effectiveness of treatment. Clarifying their mechanisms and improving their therapeutic uses should be the main goals of future studies.